2017
DOI: 10.18203/2349-3291.ijcp20170685
|View full text |Cite
|
Sign up to set email alerts
|

Solid malignant pediatric tumors: a histopathological study

Abstract: Background: In general, the features of malignancies in children differ biologically and histologically from those of adults with respect to incidence, type of tumor, underlying familial or genetic aberration and tendency to regress spontaneously or cytodifferentiation. In recent years, identification of specific genes, oncogenes, tumor markers and other biological and pathological factors have played an important role in staging and classifying risk categorization of specific tumors as low, intermediate and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…[8] In study by Gupta N et al in 2017, 40% cases were observed in 11-15 years, 31.66% in 6-10 years and 28.33% in 0-5 years. [10] In study by Monga T et al in 2017 maximum number of pediatric tumors was seen in age group of 11-14 years 41.66%. [14] Sex incidence in the present study we found male preponderance with male: female ratio of 1.2:1 for solid malignant pediatric neoplasms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[8] In study by Gupta N et al in 2017, 40% cases were observed in 11-15 years, 31.66% in 6-10 years and 28.33% in 0-5 years. [10] In study by Monga T et al in 2017 maximum number of pediatric tumors was seen in age group of 11-14 years 41.66%. [14] Sex incidence in the present study we found male preponderance with male: female ratio of 1.2:1 for solid malignant pediatric neoplasms.…”
Section: Discussionmentioning
confidence: 99%
“…Sharma S 2004 [7] Harsh Mohan 2014 [8] CT Nagaraja 2015 [9] G Vandana 2015 [6] Gupta N 2017 [10] Present study…”
Section: Sr No Type Of Malignancymentioning
confidence: 99%